Analisis Keterbukaan, Empati, dan Dukungan dalam Hubungan Single Father dan Anak: Peluang dan Tantangan - Syefira Istian Salasatikhana; Destiwati, Rita (JOM, 2024)
This study aims to analyze the interpersonal communication between single fathers and their children, focusing on three key aspects: openness, empathy, and support. The research seeks to identify the opportunities and challenges that arise in this relationship, particularly in fostering effective communication. A qualitative descriptive approach was employed, with data collected through in-depth interviews and participant observation of single fathers and their children. The analysis was conducted inductively to comprehend the communication patterns and emotional dynamics involved. The findings reveal that openness in communication is characterized by informal conversations and the sharing of daily experiences. However, obstacles often emerge due to a lack of emotional closeness or the presence of a new marriage by the father. Empathy plays a crucial role in creating strong emotional bonds, where fathers strive to understand their children's emotions, offer advice, and foster a positive atmosphere. Supportive behavior is evident through the emotional backing provided by the father, which includes freedom of expression and involvement in decision-making processes. The study concludes that openness, empathy, support, positive attitudes, and equality are the five key elements in the interpersonal communication between single fathers and their children. Each element plays a significant role in building a healthy and harmonious relationship, where openness enhances trust, empathy strengthens emotional bonds, supportive behavior fosters a sense of security, positive attitudes create an optimistic environment, and equality increases children's participation in family decision-making.